2009
DOI: 10.1007/s10493-009-9245-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vaccination with a recombinant metalloprotease from Haemaphysalis longicornis

Abstract: We report the cloning, expression and characterization of an Haemaphysalis longicornis metalloprotease (named HLMP1). The gene encodes a predicted 550 aminoacid protein with similarity to metalloproteases of the reprolysin family. The protein sequence contains a signal sequence, the zinc-binding motif (HEXXHXXGXXH) common to metalloproteases and a cysteine-rich region. Reverse transcription-PCR expression analysis indicates the presence of mRNA in the salivary gland of larva, nymph and adult ticks. Rabbit repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…As previously mentioned, vaccination with single metzincins did in fact result in some decrease of engorgement weight and ovipositioning, however, it did not have a great effect on tick mortality (Decrem et al, 2007;Imamura et al, 2009). Based on the differential transcriptional network observed between reprolysins and astacins, the results support use of a combinatorial metzincin-based vaccine, which will be evaluated in a subsequent study.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…As previously mentioned, vaccination with single metzincins did in fact result in some decrease of engorgement weight and ovipositioning, however, it did not have a great effect on tick mortality (Decrem et al, 2007;Imamura et al, 2009). Based on the differential transcriptional network observed between reprolysins and astacins, the results support use of a combinatorial metzincin-based vaccine, which will be evaluated in a subsequent study.…”
Section: Discussionsupporting
confidence: 67%
“…Spirochete dissemination through vertebrate tissues may similarly be aided by salivary metalloproteases and other salivary anti-haemostatic agents (Maritz-Olivier et al, 2007;Ribeiro, 1989), which prevent fibrin clot formation and dissolution of the fibrin clots eventually formed around the feeding cavity of ixodid ticks (Francischetti et al, 2003). For this reason both Decrem et al (2007) and Imamura et al (2009) selected salivary gland metalloproteases from I. ricinus and H.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it was proposed that I. scapularis salivary MPs inhibits microvascular endothelial cell proliferation and degrades both ␣ and ␤ subunits of integrins ␣5␤1 and ␣1␤1 (Francischetti et al, 2005;Kazimirova and Stibraniova, 2013). Previous studies using H. longicornis MP as antigen demonstrated that nymph and adult tick mortality increases (Imamura et al, 2009). In I. ricinus, inhibition of MPs expression by RNAi prevents completion of tick blood meal and impairs tick saliva fibrinolytic and fibrinogenolytic activities (Decrem et al, 2008a(Decrem et al, , 2008b.…”
Section: Discussionmentioning
confidence: 99%
“…Host vaccination with an I. ricinus recombinant MP impairs blood meal completion, besides reducing tick weight gain and oviposition rates (Decrem et al, 2008b). In Haemaphysalis longicornis, six MPs were identified, one of which was shown to be a potentially interesting immunoprotective antigen (Harnnoi et al, 2007;Imamura et al, 2009).…”
Section: Introductionmentioning
confidence: 99%